ANALISIS PENGENDALIAN KUALITAS PRODUK TAHU DI PABRIK TAHU PAK SUSILO - Panjaitan, Melva C; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2023)
Tofu factories are small and seldom have sewage treatment facilities because constructing and operating sewage treatment facilities is very expensive. A factory engaged in food production, especially tofu production. The problem at Pak Susilo's tofu factory, employees lack discipline in carrying out each production process and the semi-manual tofu-making process. As a result, the company does not have a standard or SOP (Standard Operating Procedure) in its production process, pays little attention to quality control in each of its production activities, and allows minor problems such as color damage and cutting errors. increased, Analysis using the SQC 7 Method Tool, A. with observations for 20 full days at Pak Susilo's tofu factory and consistent daily defect rates such as defects in texture damage, dirt, color damage, and incorrect reduction of texture damage by 12164 pcs or by 42 .0%, in the second place there is dirt, namely 9382 pcs or 32.4%, in the third order is color damage, which is 4471 pcs or 15.4% and the smallest damage is one of the cuts, which is 2973 or 10.3% .